Exercise motives among university students – A Brazil-Portugal transnational study - Campos, Lucas Arrais; dos Santos, Adrielly; Sampaio, Mafalda Margarida Basto; Marôco, João; Campos, Juliana Alvares Duarte Bonini (Frontiers in Psychology, 2022)
Background Identifying the motives why people exercise is interesting for the planning of effective health promoting strategies. Objectives To estimate the psychometric properties of the exercise motivations inventory (EMI-2) in Brazilian and Portuguese university students, and to compare motive-related factors for exercise among students. Methods One thousand Brazilian (randomly splitted into “Test sample” [n = 498] and “Validation sample” [n = 502]) and 319 Portuguese students participated in this cross-sectional study. Motives for exercise were evaluated using EMI-2. Exploratory factor analysis was performed in the test sample. Then, confirmatory factor analysis was performed in the validation and Portuguese samples. The EMI-2 scores were compared according to sex, exercise, and weight status (ANOVA, α = 5%). Results EMI-2 factor model was explained by 5 factors and presented adequate fit (χ2/df ≤ 3.2; CFI ≥ 0.9; TLI ≥ 0.9; RMSEA ≤ 0.07; and α ≥ 0.83). The motives for exercising were mainly related to psychological and interpersonal factors for men, health-related factors for women, and body-related factors for overweight and obese individuals. People who practice exercise had higher EMI-2 scores. Conclusion The 5-factor model is suggested for a comprehensive assessment of motives for exercise. Individual characteristics should be considered for development of tailored protocols.